Relationship of School Libraries and ICT Against the Environmental Literacy in From Five Students - Muhamad Omar; Vun, Leong Wan; Mohd Suhaimi Taat (2018)
This study aims to identify the linkages between the use of School Resource Center (SRC) and ICT in teaching and learning towards 'Environmental Literacy' students. A total of 110 respondents from form 5 students in a secondary school in Tawau, Sabah. A quantitative approach with a survey technique was used in this study. The descriptive data obtained indicate that the level of Environmental Literacy is higher than the level of ICT and SRC which is an independent variable for this study. The t-test showed that there was no significant difference in environmental literacy among secondary school students based on gender. The results also showed a positive relationship between the use of SRC and ICT with the students of 'Environmental Literacy'. The use of SRC and ICT among students can directly improve the student's literacy with their environment. Therefore, the contribution of these two facilities should be clearly recognized by all parties so that the facilities can be enhanced and not taken into account especially on students. In conclusion, SRC and ICT are not just an easy-to-access facility for students but it is the best medium or platform for them to apply it in order to strengthen the environment literacy among of them.